Pemikiran Ibnu Miskawaih Tentang Konsep Pendidikan Karakter Akhlak - Ujud Supriaji (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2021)
Abstract Ibn Miskawaih is a Muslim scholar who concentrates on the field of moral philosophy. He was born in Iran in 330 AH/932 AD and died in 421 AH/1030 AD. The formulation of the problem from this research is How is the Biography of Ibn Miskawaih?, What are the works of Ibn Miskawaih? What is the concept of Ibn Miskawaih's moral thought? This study aims to describe the biography of Ibn Miskawaih, to describe what Ibn Miskawaih's works are, and how Ibn Miskawaih thinks about the concept of character education. He was born in Iran in 330 H/932 AD and died in 421 H/1030 AD. According to Ibn Miskawaih, morality is the state of a person's soul that encourages him to perform actions without prior thought. The characteristics of Ibn Miskawaih's thought in moral education in general begin with a discussion of morals (character/character). According to him, there is a character that is natural and there is a character that is acquired through habit or practice. He thinks that these two characters are essentially unnatural even though we are born with our own character, but actually character can be cultivated through education and teaching. Keywords: Ibn Miskawaih, Biography, Thought